Financial Risks in Toll Road Development in Indonesia: Challenges and Development Strategies for the Probowangi Toll Road - Azis, Aminudin (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
Probolinggo-Banyuwangi toll road, which crosses mountainous areas in East Java. Toll road construction in areas with varying topography often faces significant technical and environmental challenges, which can affect costs, completion time, and project sustainability. This study uses a quantitative approach with a descriptive method to evaluate risk factors that impact project finances, such as construction costs, dependence on funding sources, interest rate fluctuations, and traffic volume predictions. Primary data was collected through questionnaires, while secondary data was obtained from financial planning documents and related project topography. Data analysis was conducted using multiple linear regression with a path analysis model. The results of this study are expected to identify key variables that influence financial risk and provide recommendations for effective mitigation strategies. This research is expected to contribute to the development of policies and financial risk management practices for similar infrastructure projects in the future.